Oxytocin Protects Against Isoproterenol-Induced Cardiac Hypertrophy by Inhibiting PI3K/AKT Pathway via a lncRNA GAS5/miR-375-3p/KLF4-Dependent Mechanism - Yang, Yuqiao; Wang, Zhuoran; Yao, Mengran; Xiong, Wei; Wang, Jun; Fang, Yu; Yang, Wei; Jiang, Haixia; Song, Ning; Liu, Lan; Qian, Jinqiao (Frontiers in Pharmacology, 2021)
Cardiac hypertrophy is caused by cardiac volume or pressure overload conditions and ultimately leads to contractile dysfunction and heart failure. Oxytocin (OT), an endocrine nonapeptide, has been identified as a cardiovascular homeostatic hormone with anti-hypertrophic effects. However, the underlying mechanism remains elusive. In this study, we aimed to investigate the role and mechanism of OT in cardiac hypertrophy. The rats with cardiac hypertrophy induced by isoproterenol (ISO) were treated with or without oxytocin. Cardiac functional parameters were analyzed by echocardiography. The changes in cell surface area were observed using wheat germ agglutinin (WGA) or immunofluorescence staining. The expressions of cardiac hypertrophy markers (B-Natriuretic Peptide, BNP and β-myosin heavy chain, β-MHC), long non-coding RNA Growth (LcRNA) Arrest-Specific transcript 5 (lncRNA GAS5), miR-375-3p, and Kruppel-like factor 4 (Klf4) were detected by qRT-PCR. KLF4 protein and PI3K/AKT pathway related proteins were detected by Western blot. The interactions among lncRNA GAS5, miR-375-3p, and Klf4 were verified by dual-luciferase reporter assays. The findings showed that OT significantly attenuated cardiac hypertrophy, increased expressions of lncRNA GAS5 and KLF4, and decreased miR-375-3p expression. In vitro studies demonstrated that either knock-down of lncRNA GAS5 or Klf4, or over-expression of miR-375-3p blunted the anti-hypertrophic effects of OT. Moreover, down-regulation of lncRNA GAS5 promoted the expression of miR-375-3p and inhibited KLF4 expression. Similarly, over-expression of miR-375-3p decreased the expression of KLF4. Dual-luciferase reporter assays validated that lncRNA GAS5 could sponge miR-375-3p and Klf4 was a direct target gene of miR-375-3p. In addition, OT could inactivate PI3K/AKT pathway. The functional rescue experiments further identified OT regulated PI3K/AKT pathway through lncRNA GAS5/miR-375-3p/KLF4 axis. In summary, our study demonstrates that OT ameliorates cardiac hypertrophy by inhibiting PI3K/AKT pathway via lncRNA GAS5/miR-375-3p/KLF4 axis.